TYPOGRAPHY ON DESIGN T SHIRT SUPORTER OF PERSIB - Muhammad Hidayatulloh; Iman Somargono (Universitas Kuningan, 2018)
AbstractAs a type of clothing used in daily life, a t shirt at this time often displays images and text on the surface. Picture or text in a t shirt, can act as aesthetic element or a form of expression as well as identity for the wearer. For the supporters of Persib, t shirt becomes one of the attributes that they often use in supporting Persib both in the field and off the field. T Shirt of the supporters, generally uses text elements as part of the design elements and conveys messages to support Persib. Text on t shirt supporters of Persib, is packed in such a way to attract the attention of the audience. In the perspective of typography, the letters in the text not only play a role in preparing a textual message but also it can present a visual perception that is able to support the message containing and attract the attention of the audience.Keywords: t shirt, supporter, persib, typography